CYTOKINE-MEDIATED BRAIN DYSFUNCTION: INTEGRATING IMMUNOLOGICAL MECHANISMS AND PSYCHIATRIC PATHOPHYSIOLOGY FOR TRANSLATIONAL INSIGHTS AND PRECISION THERAPEUTICS (Global Conference on Medical and Health Sciences, 2026)
Cytokines, as key mediators of immune signaling, have emerged as critical regulators of brain function and dysfunction, bridging the fields of immunology and psychiatry. Increasing evidence suggests that dysregulated cytokine activity contributes to the development and progression of various psychiatric disorders, including major depressive disorder, schizophrenia, and bipolar disorder. This growing body of research challenges traditional neurotransmitter-centered models and highlights the role of immune mechanisms in shaping mental health outcomes.